Implementation of Filling Primary High Leadership Positions through A Job Fit Test in Jambi Provincial Government, Indonesia - sri hartati; Rikha Muliasari; Andri Tri Madan (Institut Pemerintahan Dalam Negeri, 2022)
The Job Fit Test for Primary High Leadership Positions in the Jambi Provincial Government was conducted to obtain competent Primary High Leadership officials. This research aims to analyze and describe the implementation of filling the Primary High Leadership Positions through the Job Fit Test in the Jambi Provincial Government and determine the associated obstacles and efforts needed to overcome them. This is a descriptive qualitative research with the implementation analysis used to investigate the Communication, Disposition, Resources, and Bureaucratic Structure. The results showed that the strategy used to fill the Primary High Leadership Positions is running well but still requires improvements in the aspects of Resources and Bureaucratic Structure. The obstacles experienced are the unavailability of supporting facilities and infrastructure in the form of buildings and the lack of proper government regulation. One of the efforts to overcome these obstacles is using the Jambi Province Human Resources Development Agency building for Primary High Leadership candidates and preparing a government regulation. Keywords: Job Fit; Competency Test; Primary High Leadership Positions Abstrak Uji Kesesuaian (Job Fit) Jabatan Pimpinan Tinggi Pratama di Pemerintah Provinsi Jambi dilaksanakan untuk memperoleh pejabat Pimpinan Tinggi Pratama yang kompeten. Tujuan penelitian ini untuk menganalisis dan mendeskripsikan implementasi pengisian Jabatan Pimpinan Tinggi Pratama melalui Uji Kesesuaian (Job Fit) di Pemerintah Provinsi Jambi, hambatan dan upaya mengatasinya. Metode yang digunakan adalah deskriptif kualitatif. Selanjutnya dilakukan analisis implementasi dengan aspek yang diteliti, antara lain: Komunikasi, Disposisi, Sumber Daya dan Struktur Birokrasi. Hasil penelitian ini menunjukkan bahwa Implementasi Pengisian JPT Pratama melalui Uji Kesesuaian (Job Fit) secara keseluruhan berjalan dengan baik, namun masih memerlukan peningkatan pada aspek Sumber Daya dan Struktur Birokrasi. Hambatan yang dialami yaitu: fasilitas sarana dan prasarana penunjang berupa gedung belum tersedia dan belum dibentuk Peraturan Gubernur yang mengatur tentang teknis Pengisian Jabatan Pimpinan Tinggi Pratama melalui Uji Kesesuaian (Job Fit). Upaya mengatasi hambatan yaitu: menggunakan gedung BPSDM Provinsi Jambi untuk pelaksanaan kegiatan Uji Kesesuaian (Job Fit) calon pejabat Pimpinan Tinggi Pratama dan menyusun Peraturan Gubernur tentang teknis Pengisian Jabatan Pimpinan Tinggi Pratama melalui Uji Kesesuaian (Job Fit). Kata Kunci: Job Fit; Uji Komptensi; JPT Pratama